1993
DOI: 10.1002/mrm.1910290209
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of water‐macromolecule proton magnetization transfer in articular cartilage

Abstract: These studies were designed to establish which structural elements of cartilage are responsible for proton magnetization transfer between water (Hf) and macromolecules (Hr) observed in MRI studies on articular cartilage. Saturation transfer techniques were used to monitor magnetization transfer in vitro on samples of the two major constituents of cartilage: collagen and proteoglycan. Articular cartilage samples were also evaluated in vitro before and after the removal of the proteoglycan fraction. Isolated hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(122 citation statements)
references
References 19 publications
6
116
0
Order By: Relevance
“…In vivo applications of MTC in human diseases other than atherosclerosis [50,51] have also reported a linear correlation between MT and tissue collagen concentration. The importance of collagen in creating an MT effect is evident by the fact that although this single macromolecule comprises only ~ 40% of the macromolecules in cartilage, it is responsible for nearly all of the MT effect observed [39,41]. Moreover, several other mechanisms contribute to the rate of MT, including the mobility, the hydration state and the number of hydroxyl and amide groups [40], as well as the concentration of the macromolecules and/or water [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo applications of MTC in human diseases other than atherosclerosis [50,51] have also reported a linear correlation between MT and tissue collagen concentration. The importance of collagen in creating an MT effect is evident by the fact that although this single macromolecule comprises only ~ 40% of the macromolecules in cartilage, it is responsible for nearly all of the MT effect observed [39,41]. Moreover, several other mechanisms contribute to the rate of MT, including the mobility, the hydration state and the number of hydroxyl and amide groups [40], as well as the concentration of the macromolecules and/or water [51].…”
Section: Discussionmentioning
confidence: 99%
“…These conditions were previously optimized in our lab using phantoms and carotid endarterectomy specimens [37]. MT employs an off-resonance pulse that selectively saturates the water molecules bound to macromolecules compared to those in the free water pool, resulting in images with reduced signal intensity that is proportional to the amount of macromolecules [39-41]. Finally, 2D DW images were acquired with: TR = 1 s, TE = 25 ms, Δ = 12.6 ms, δ = 5 ms, averages = 32, slice thickness = 1 mm, matrix = 128 × 128, and FOV = 6.5 mm (spatial resolution = 50 × 50 μm), scan time = 6.5 h. The apparent diffusion coefficient (ADC) was calculated from seven b-values = 0, 196, 442, 637, 867, 1770 and 2409 s/mm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…37 Other areas of application for MT that are less well established include breast, 38 knee 39 and cartilage. 40 Within cartilage, it may be possible using Gd-DTPA to separate the effect of proteoglycan degradation, from the effect of collagen disruption, which is the major contributor to MT in this tissue (Deb. Burstein, MIT, private communication).…”
Section: Applications In Imagingmentioning
confidence: 99%
“…It is nonionizing, offers multiplanar capabilities, has high spatial resolution, and provides superior depiction of soft tissue detail. In addition to evaluation of articular cartilage volume, thickness, and degeneration (9)(10)(11)(12)(13)(14), recent advances have made it possible to use MRI to assess bony and soft tissue changes. In a guinea pig model, results showed that MR images of trabecular bone accurately reflected the degree of osteopenia and the development of subchondral sclerosis and osteophytes (15).…”
mentioning
confidence: 99%